Lithuania in the Context of Sustainable Development - Leiputė, Beatričė (Lithuanian Journal of Statistics, 2014)
The goal of this paper is to analyze the tendencies of social exclusion and inequality in Lithuania and in the context of Europe. By using statistical methods such as Gini coeﬃcient and Lorenz curve, ﬁrstly we analyze the inequality of average county disposable household income per month. In the second part of the study, we analyze an indicator of people at-risk-of poverty or social exclusion in 26 diﬀerent countries of Europe. In this section, we want to test the ﬁxed and random eﬀects models on our data. Based on them, the average eﬀect of the at-risk-of poverty or social exclusion indicator can be measured. Based on real expenditure per capita analysis, Lithuania can be classiﬁed to a group of post-Soviet countries, where tendencies of poverty or social exclusion risk are similar.
Keywords: sustainability; inequality; social exclusion; poverty; Gini coeﬃcient; Lorenz curve; panel data models